Investigation of the gelation mechanism between amino acid surfactant based microemulsion and kappa-carrageenan gel network - Nasima Akter,; Shahidan Radiman,; Faizal Mohamed,; Nazaruddin Ramly,; Edy Giri Rachman Putra,; Ari Sulistyo Rini, (Universiti Kebangsaan Malaysia, 2014)
Kappa-carrageenan is one form of necessary hydrocolloid. Hydrocolloids are macromolecular materials, which swell upon absorption of water; in some cases, forming a stiff gel in the presence of additives. This property is very important to suspend nanocarriers into gel network, which provide them long time stability at a varying temperature range. In this work, we prepared microemulsion and trapped these particles inside the kappa-carrageenan gel network. The microemulsion was composed of sodium N-lauroylsarcosinate hydrate (SNLS), oleic acid and deionized water. The purpose of this study was to immobilize them into the gel network, giving longer shelf life at a range of temperatures for oral drug delivery. Morphological properties were investigated by transmission electron microscope (TEM), dynamic light scattering (DLS) and Fourier transform infrared (FTIR) spectra. The TEM results showed that microemulsions are trapped in the gel network, and the diameter of the microemulsions are below 100 nm, which is comparable with the DLS results. The important functional groups of kappa-carrageenan and microemulsion were shown from the FTIR result of the complex microemulsion gel. These results confirmed the interaction between SNLS based microemulsion and kappa-carrageenan gel.